2020
DOI: 10.1186/s12909-020-1926-y
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based mastery learning compared to standard education for discussing diagnostic uncertainty with patients in the emergency department: a randomized controlled trial

Abstract: Background: Diagnostic uncertainty occurs frequently in emergency medical care, with more than one-third of patients leaving the emergency department (ED) without a clear diagnosis. Despite this frequency, ED providers are not adequately trained on how to discuss diagnostic uncertainty with these patients, who often leave the ED confused and concerned. To address this training need, we developed the Uncertainty Communication Education Module (UCEM) to teach physicians how to discuss diagnostic uncertainty. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…There is overlap with general uncertainty communication, and existing educational materials related to other, non-obstetric situations could be leveraged and adapted to the FTB scenario. These might include, for instance, the Uncertainty Communication Checklist or simulation-based mastery learning geared towards uncertainty ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is overlap with general uncertainty communication, and existing educational materials related to other, non-obstetric situations could be leveraged and adapted to the FTB scenario. These might include, for instance, the Uncertainty Communication Checklist or simulation-based mastery learning geared towards uncertainty ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The trial methods are described in detail in the published trials protocol manuscript. 18 In brief, we conducted a randomized controlled waitlist trial from September 2021 to June 2022 across 2 urban academic residency training sites: Thomas Jefferson University (TJU) and Northwestern University (NU). TJU Hospital, the main TJU clinical site, is an urban academic hospital located in Philadelphia, Pennsylvania, with approximately 100,000 ED visits annually.…”
Section: Methodsmentioning
confidence: 99%
“…In this article, we report results from a randomized controlled waitlist trial testing UCEM efficacy for teaching physicians to achieve mastery as assessed by the UCC. 18 We hypothesized that physicians who received immediate access to the UCEM intervention would be significantly more likely to achieve mastery (i.e., meeting or exceeding the minimum passing standard set for the UCC) on their first attempt at the initial posttest compared with physicians whose access was delayed.…”
mentioning
confidence: 99%
“…One of the possible explanations is that HPs may have been trained in how to discuss diagnostic uncertainty with their patients. Although there are no standard instructions and approaches to discussing uncertainty for patients discharged from the ED with diagnostic uncertainty (McCarthy et al, 2020), recent studies have reported on the inclusion of training in how to discuss diagnostic uncertainty with patients in medical degree programs (McCarthy et al, 2020;Poluch et al, 2022). Specifically, medical students are instructed to explicitly tell patients that there is no confirmed explanation (diagnosis) for what the patient has been experiencing (McCarthy et al, 2020;Poluch et al, 2022).…”
Section: Health Practitioner Talkmentioning
confidence: 99%